Transformasi Pendidikan Agama Islam Dalam Mewujudkan Generasi Berkarakter di Kawasan Rawan Penyimpangan Sosial - Jumaida Rahmadani; Betti Megawati; Rahmi Syafriyeti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the form and implementation of the transformation of Islamic Religious Education (PAI), the process of internalizing Islamic values, as well as the effectiveness and supporting and inhibiting factors in creating a generation of character at the Peace Education Foundation School. This study uses a qualitative approach with a phenomenological type. Data collection was conducted through observation, in-depth semi-structured interviews, and documentation with triangulation techniques. Data analysis used an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results show that the transformation of PAI has shifted from a conventional cognitive-oriented approach to a holistic, integrative, and humanistic approach that includes affective and psychomotor aspects. The process of internalizing values occurs gradually through the stages of knowing, understanding, internalizing, and acting, supported by teacher role models and the religious culture in the school environment. This transformation has an impact on more positive changes in student behavior, increased involvement in religious activities, and strengthened moral awareness. Supporting factors include teacher commitment, structured religious programs, and a religious school culture, while inhibiting factors include external environmental influences, limited learning time, and low involvement of some parents